Preliminary Study on High-Energy and Low-Energy Microfracture Event Evolution Characteristics in the Development Process of Rock Failure. (14th September 2020) - Yu, Guofeng; Cheng, Guanwen; Li, Lianchong; Tang, Chunan; Ren, Bo; Han, Yunchun
Abstract : The evolution characteristics of high-energy and low-energy microfracture events play an important role in the brittle failure mechanism of rock and reasonable microseismic (MS) monitoring and acoustic emission (AE) monitoring. The bimodal distribution (BMD) model is commonly used to observe the evolution characteristics of high-energy and low-energy MS events; however, its precise mechanism remains unclear. The evolution characteristics of high-energy and low-energy microfracture events are assessed in this study based on a BMD model. MS monitoring results from the No. 22517 working face of the Dongjiahe Coal Mine are studied, and AE monitoring results of a biaxial compression experiment of a granite specimen are analyzed. High-energy MS events in the No. 22517 working face are found to be generated by an increase in the failure scale of the overlying rock mass upon exiting the insufficient mining stage and entering the sufficient mining stage. The change characteristics of the high-energy AE hits are positively correlated with crack evolution characteristics in the granite specimen and negatively correlated with changes in the Gutenberg-Richter b value. A precise high-energy and low-energy AE hit evolution mechanism is analyzed based on the microscopic structure of the granite specimen. Similarities and differences between high-energy MS events and low-energy AE hits are determined based on these results. Both are found to have bimodal characteristics; an increase in the failure scale is identified as the root cause of the high-energy component. The bimodal distribution of AE hits is far less obvious than that of MS events.